Analisis Aktivitas Antibakteri Ekstrak Daun Kelor (Moringa oleifera Lam.) Terhadap Pertumbuhan Pseudomonas aeruginosa - Rahmah, Windya Nazmatur; Ramdhani , Fitria Hariati; Hanida , Luthfiani; Sartika, Fera (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Moringa leaves (Moringa oleifera Lam.) are known to have various health benefits, one of which is their potential as an antibacterial agent. This study aims to activate the antibacterial activity of moringa leaf extract against the growth of Pseudomonas aeruginosa. The test was carried out with five treatments, namely moringa leaf extract with concentrations of 15%, 30%, 50%, positive control, and negative control. The well diffusion method was used in the test, with incubation at 37°C for 24 hours. The diameter of the inhibition zone was measured as an indicator of effectiveness. The results showed that a concentration of 15% did not produce an inhibition zone, while concentrations of 30% and 50% showed an average inhibition zone of 0.87 mm and 2.85 mm, respectively. Based on the CLSI criteria, all results were divided into resistant because the size of the inhibition zone was ≤ 15 mm. Thus, it can be concluded that moringa leaf extract has not shown optimal effectiveness in inhibiting the growth of Pseudomonas aeruginosa..